Solve the following system of equation by the method of cross-multiplication:

Asked by nkrbasak | 23rd Sep, 2010, 02:59: PM

Expert Answer:

Dear student,
Following is the answer to your query:
 
The given equations can be written as:
(a - b)x + (a + b)y - (2a2 - 2b2) = 0
(a + b)x + (a + b)y - 4ab = 0
 
Compairing the above equations with the equations:
a1x + b1y + c1 = 0, a2x + b2y + c2 = 0
we get
a1 = (a - b), b1 = (a + b), c1 = -(2a2 - 2b2)
a2 = (a + b), b2 = (a + b), c2 = - 4ab
 
Substitue these values in the following:
 
Note: If the method of solving these equations is not given, then you can easily solve these equations by eliminating the variable y as the coefficient of y is same in both the equations.
 
Regards,
TopperLearning

Answered by  | 24th Sep, 2010, 10:21: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.